PERAN PENGRAJIN LOKAL DALAM PENGEMBANGAN WISATA EDUKASI TENUN CUAL DI KABUPATEN SAMBAS - Oggy Akmadani (CV. ADIBA AISHA AMIRA, 2026)
This study analyzes the role of local artisans in developing educational tourism based on Cual weaving in Sambas Regency, focusing on Sumber Harapan Village as a weaving center with cultural assets, craft products, and hands-on learning activities. This article applies a descriptive qualitative approach by reviewing field data derived from observation, interviews, documentation, and secondary data from previous research on the development of Cual weaving educational tour packages. Data were analyzed through reduction, display, and conclusion drawing. The findings show that local artisans act as custodians of traditional knowledge, key actors in educational attractions, cultural interpreters, souvenir product innovators, and connectors between cultural heritage and tourist experience. These roles are reflected in the demonstration of terau, liring, penganian, menatar, mengubung, motif design, and weaving processes, which can be packaged as learning-based tourism activities. Artisans also strengthen the tourism value chain through weaving galleries, workshops, product sales, and simple weaving assistance for visitors. However, the development of educational tourism still requires stronger interpretation skills, service standards, package variation, digital promotion, and clearer partnerships among artisans, tourism awareness groups, village government, and tourism stakeholders. This article argues that the success of Cual weaving educational tourism depends not only on the existence of woven products, but also on the positioning of artisans as central subjects in designing meaningful tourism experiences.